Usable Security of Online Banking Authentication: An Exploratory Factor Analysis - Mujinga, Mathias (Journal of Information System and Informatics, 2024)
The usability and security of information system applications significantly affect the users willingness to adopt the applications; online banking is one such service. The emergence of innovative technologies in all facets of our daily activities makes usable security critical to protect users’ privacy and personal information. The paper aims to investigate the usability and security of the online banking authentication process. The study is based on users’ perceptions of the login system of their respective banks' online banking services, using the attitude questionnaire statements related to usability and security aspects of the authentication process. The paper presents the results of 1190 survey responses in South Africa. The findings show that younger and inexperienced users are not satisfied with the usability of online banking authentication systems as they scored the system very low compared to the older and experienced users. Given the prevalence of online security breaches, improving the authentication process' usability will help create a secure online environment.